Evaluating the Radiation From Accidental Exposure During a Nondestructive Testing Event. Issue 2 (August 2015) - Ting, Chien-Yi; Wang, Hsin-Ell; Lin, Jao-Perng; Lin, Chun-Chih
Abstract : Abstract: Industrial radiography is a common nondestructive testing (NDT) method used in various industries. An investigation was conducted for a 1999 incident in Taiwan where two workers (Operators A and B) were accidently exposed to an unshielded 192 Ir source while conducting industrial radiography. Operators A and B experienced acute close-range radiation exposure to a source of 192 Ir for 3 h at a strength of 2.33 × 10 12 Bq. The health of mammary glands, bone marrow, thyroid glands, eyes, and genital organs of these two workers after radiation exposure was examined. Subsequently, Operator A experienced severe radiation injury, including tissue necrosis and keratinization in the fingers, chromosomal abnormalities, reduced blood cell count, diffuse hyperplasia of the thyroid gland, opaque spots in the crystalline lens, and related radiation effects. The results showed that the left index finger and thumb, eyes, and gonads of Operator A were exposed to a radiation dose of about 369–1, 070, 23.1–67.4, 2.4–5.3, and 4.2–11.6 Gy, respectively. Effective dose for Operator A was estimated to range from 6.9 to 18.9 Sv. The left fingers, thumb, eyes, and gonads of Operator B were exposed to a radiation dose of 184.9–646.2, 11.8–40.7, 0.49–3.33, and 0.72–7.18 Gy, respectively, and his effective dose was between 2.5 and 11.5 Sv. This accident indicated a major flaw in the control and regulation of radiation safety for conducting NDT industrial radiography in 1999; however, similar problems still exist. Modifications of the Ionizing Radiation Protection Act in Taiwan are suggested in this study to regulate the management of NDT industries, continually educate the NDT workers in radiation safety, and enact notification provisions for medical care systems toward acute radiation exposure events.